TAFSIR KRITIS TERHADAP RUT 1:1-22: Menggali Makna Loyalitas Di Tengah Tantangan Sosial Budaya - Simatupang, Jhonnedy Kolang Nauli; Romi, Romi (Sekolah Tinggi Agama Kristen Luwuk Banggai, 2024)
This study aims to analyze how Ruth's loyalty in the Book of Ruth reflects a deep spiritual commitment and its relevance as a model of devotion to God amidst social and cultural challenges. As a Moabite facing social stigma, Ruth's loyalty to Naomi and the God of Israel demonstrates devotion that transcends ethnic and traditional boundaries. This research employs a qualitative method with a textual criticism approach to analyze the text of the Book of Ruth. Data collection was conducted through a literature review, including the Bible text, commentaries, and related academic articles. Data analysis involved textual criticism to interpret symbolic meaning, language use, and historical context within Ruth’s narrative. The study reveals that Ruth’s loyalty embodies khesed, or steadfast love, which represents not only a spiritual commitment to God but also tangible devotion to her community and those around her. Ruth's model of devotion is relevant to modern society, which faces challenges of diversity and tolerance. These findings enrich the understanding of the relationship between spiritual commitment and social influence in a religious context.